The Role of Lunate Morphology on Scapholunate Instability and Fracture Location in Patients Treated for Scaphoid Nonunion - Kim, Byoung-Jin (Clin Orthop Surg, 2016)
BACKGROUND: To determine the association between lunate morphology and the scapholunate instability using radiographic images, and investigate the association between lunate morphology and scaphoid fracture location. METHODS: Between January 2003 and December 2011, we retrospectively evaluated the plain radiographs and computed tomography (CT) images of 70 patients who underwent surgical intervention for a scaphoid nonunion, in order to determine the association between lunate type (I or II) and scapholunate instability or scaphoid fracture location. We determined the scaphoid fracture location using the fragment ratio and measured the radiolunate angle and capitate-triquetrum (C-T) distance. RESULTS: A type II lunate was present in 68.6% (48 of 70 cases). Mean fragment ratio of fracture location was 50.6% in the type II lunate group and 56.2% in the type I lunate group (p = 0.032). Sixteen of the 70 patients had dorsal intercalated segmental instability (DISI) deformities. Nine of 22 cases showed DISI deformity in type I lunate and 7 of 48 cases showed DISI deformity in type II lunate (p = 0.029). However, there were no significant differences between the presence of DISI deformity and fracture location (p = 0.15). Morphologic comparisons by both plain radiography and CT indicated a mean C-T distance in the type I lunate group (22 cases) of 2.3 mm and 5.0 mm in the type II lunate group (48 cases). The C-T distances were significantly correlated with lunate morphology (p = 0.001). CONCLUSIONS: A type II lunate was associated with low incidence of DISI deformity and proximal location of fracture in patients presenting with a scaphoid nonunion.